2012
DOI: 10.2147/ott.s30609
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of human breast tumors in NOD/SCID mice by CD44 shRNA gene therapy combined with doxorubicin treatment

Abstract: BackgroundBreast cancer stem cells with a CD44+CD24− phenotype are the origin of breast tumors. Strong CD44 expression in this population indicates its important role in maintaining the stem cell phenotype. Previous studies show that CD44 down-regulation causes CD44+CD24− breast cancer stem cells to differentiate into non-stem cells that are sensitive to antitumor drugs and lose many characteristics of the original cells. In this study, we determined tumor suppression in non-obese severe combined immunodeficie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 63 publications
0
12
0
Order By: Relevance
“…They identified and isolated a small subset of cells within primary breast cancer cells of which a few cancer cells were able to form palpable tumors in the mammary fat pad of non-obese diabetic/severe combined immunodeficient (NOD/SCID) mice. Such cells express CD44 or CD44 with epithelial specific antigen (ESA), but not CD24, consistent with the phenotypic characteristics of mammary stem cells with multipotent differentiation ability [33, 34]. Nevertheless, although these results demonstrate the possibility that BCSCs originate from the normal mammary stem cells, it is generally accepted that further genomic profiling and comparison of the normal stem cells versus BCSCs should provide insightful information on the aggressive phenotype of BCSCs.…”
Section: The Concept Of Cscs and Self-renewalmentioning
confidence: 69%
“…They identified and isolated a small subset of cells within primary breast cancer cells of which a few cancer cells were able to form palpable tumors in the mammary fat pad of non-obese diabetic/severe combined immunodeficient (NOD/SCID) mice. Such cells express CD44 or CD44 with epithelial specific antigen (ESA), but not CD24, consistent with the phenotypic characteristics of mammary stem cells with multipotent differentiation ability [33, 34]. Nevertheless, although these results demonstrate the possibility that BCSCs originate from the normal mammary stem cells, it is generally accepted that further genomic profiling and comparison of the normal stem cells versus BCSCs should provide insightful information on the aggressive phenotype of BCSCs.…”
Section: The Concept Of Cscs and Self-renewalmentioning
confidence: 69%
“…The cells were transfected with green fluorescent protein (GFP) using a lentiviral vector, as per the previous protocol (Van Pham et al, 2012). The GFP-BCSCs were grown in cell culture medium (DMEMF12/10% FBS/1% antibiotic-antimycotic) and incubated at 37 o C in a humidified atmosphere with 5% CO2.…”
Section: Breast Cancer Stem Cell Isolation and Proliferationmentioning
confidence: 99%
“…However, the latter study (19) also reported that patients with tumors containing high numbers of CD44 + /CD24 − cells more frequently developed bone metastases in the course of the disease. The molecular mechanisms underlying the roles of breast CSCs in chemoresistance have been reported in several studies (20,21) and proposed clinical implication for breast cancer therapeutics (22)(23)(24)(25). The occurrence of a fraction of breast CSCs with increased multidrug resistance (MDR) affinity clinically may be an additional mechanism for the positive selection of breast CSCs during chemotherapy (20).…”
Section: Discussionmentioning
confidence: 99%